The distribution of allied dental practitioners in australia: socio‐economics and rurality as a driver of better health service accessibility. (17th February 2019) - Jean, G; Kruger, E; Tennant, M
Abstract: Objectives: Analysis of the distribution of allied dental practitioners relative to the socio‐economic profile of the population, to develop a baseline of employment demographics at a time of proposed deregulation of practicing restrictions. Methods: A database of allied dental practitioners (ADP – oral health therapists, dental therapists and dental hygienists) was compiled from the public access register of the Australian Health Practitioner Regulation Agency. The principal practice locations limited to suburb and postcode were geocoded by latitude and longitude and superimposed on a map of the Australian landmass using QGIS software. Using Australian Bureau of Statistics data, the number of ADPs for each Statistical Area 2 (SA2) was counted and apportioned according to proportion of the population within each SA2 for each quintile of the Index of Relative Socio‐economic Disadvantage (IRSD). The results were reported according to oral health therapists, dental therapists and dental hygienists per 100 000 population for each IRSD quintile, by state and territory, and the Australian Regional Index for Areas (ARIA+). Results: The ADP to population ratio was not consistent for each professional class between states and territories, IRSD quintiles and (ARIA+) regional areas. Across major cities, South Australia was the state with the highest ratio of oral health therapists (10.6–12.9) and dental hygienists (14.6–24.5) for all IRSD quintiles. Western Australia had the highest ratio of dental therapists (9.3–16.0), Conclusion: There is no consistent pattern of distribution of ADPs relative to the socio‐economic profile of the population across states and territories, and regional (ARIA+) areas of Australia.